Development of grouped icEEG for the study of cognitive processing - Kadipasaoglu, Cihan M.; Forseth, Kiefer; Whaley, Meagan; Conner, Christopher R.; Rollo, Matthew J.; Baboyan, Vatche G.; Tandon, Nitin (Frontiers in Psychology, 2015)
Invasive intracranial EEG (icEEG) offers a unique opportunity to study human cognitive networks at an unmatched spatiotemporal resolution. To date, the contributions of icEEG have been limited to the individual-level analyses or cohorts whose data are not integrated in any way. Here we discuss how grouped approaches to icEEG overcome challenges related to sparse-sampling, correct for individual variations in response and provide statistically valid models of brain activity in a population. By the generation of whole-brain activity maps, grouped icEEG enables the study of intra and interregional dynamics between distributed cortical substrates exhibiting task-dependent activity. In this fashion, grouped icEEG analyses can provide significant advances in understanding the mechanisms by which cortical networks give rise to cognitive functions.